The Results of the Mass Immunization Program against Rotavirus Infection of Children of the First year of Life in a Separate Territory of the Moscow Region - L. V. Feklisova; R. F. Shapovalova (Эпидемиология и вакцинопрофилактика)
Relevance. The rotavirus infection (RI) is one of the leading causative agent in the structure of acute enteric infections, established etiology. Long term epidemiological monitoring RI was shown that Podolsk-city in Moscow region was unfavorable place concerning prevalence of RI. Aims. Studying epidemiological efficiency and collective immunization safety of infancy children in Podolsk-city, Moscow region. Materials and methods. Registration rates of this morbidity and coverage of RI prophylactic immunization were analyzed on the basis of formal registration forms, epidemiological detection cards, out-patient cards for observation over a patients, medical reports, case register in policlinics and hospitals, vaccination documents (f. № 5, f. № 6, f. 025/a, f. 058/a, f. 060/a, f. 063/a, f. 064/a). RI data have been provided over a period of time from 2008 to 2018. Data coverage of vaccination have been given from 2015 to 2018. Used method is statistic observation. Results. Vaccination program concerning RI has been implemented in Podolsk-city from 2008 till 2018. Babies at breast in their first being were vaccinated. Live pentavalent was used for immunization. The coverage target contingent of vaccination reached 68%. This preparation was withstood by children well, unwanted effects and intestines invaginations during the vaccination were not registered. During vaccination, the number children gone to hospital with acute intestinal infections was decreasing annually. The number of children to hospital admissions at the age of one year decreased from 15.8 to 12.5%, at the age of 2–3 decreased from 43.8 to 36.3%, with small increase in specific weight of patients of an age group of 7–14 years from 7.70 to 11.2%, but at the reduced total number of inpatients of this age category. Reduction of RI morbidity marked as in target age group as in another groups which were not vaccinated. Thus, formation of population benefits was confirmed. Conclusion. Clinicoepidemiologic research paper was studied in 2014–2018 allowed to make a conclusion that the cohort immunization of infancy children with the rotavirus infection, contributes to decreasing rate morbidity in certain territory Moscow region which had surpassing factors of this infection in comparison with other cities. The number of covering collective immunization was not lower 60% of infancy children and assisted falling enteric infections in their 0–6 years, made a big impression on reducing of acute intestinal diseases among all age groups during immunization implementation company within three years.